Acute impact of recovery on the restoration of cellular immunological homeostasis - Wahl, P.; Mathes, S.; Bloch, W.; Zimmer, P. (International Journal of Sports Medicine, 2020)
In view of the growing amount of (intense) training in competitive sports, quick recovery plays a superior role in performance restoration. The aim of the present study was to compare the effects of active versus passive recovery during high-intensity interval training (HIIT) and sprint interval training (SIT) protocols on acute alterations of circulating blood cells. Twelve male triathletes/cyclists performed 1) a HIIT consisting of 4×4 min intervals, 2) a SIT consisting of 4×30s intervals, separated by either active or passive recovery. Blood samples were collected immediately before and at 0`, 30`, 60` and 180` (minutes) post-exercise. Outcomes comprised leukocytes, lymphocytes, neutrophils, mixed cell count, platelets, cellular inflammation markers (neutrophil/lymphocyte-ratio (NLR), platelet/lymphocyte-ratio (PLR)), and the systemic immune-inflammation index (SII). In view of HIIT, passive recovery attenuated the changes in lymphocytes and neutrophils compared to active recovery. In view of SIT, active recovery attenuated the increase in leukocytes, lymphocytes and absolute mixed cell count compared to passive recovery. Both protocols, independent of recovery, significantly increased NLR, PLR and SII up to 3h of recovery compared to pre-exercise values. The mode of recovery influences short-term alterations in the circulating fraction of leukocytes, lymphocytes, neutrophils and the mixed cell count, which might be associated with different hormonal and metabolic stress responses due to the mode of recovery.